Clinical efficacy of emollients in atopic dermatitis patients – relationship with the skin microbiota modification - Seité S; Zelenkova H; Martin R (Dove Medical Press, 2017)
Sophie Seité,1 Hana Zelenkova,2 Richard Martin3 1La Roche-Posay Dermatological Laboratories, Asnières, France; 2DOST, Private Clinic of Dermatovenereology, Svidnik, Slovakia; 3L’Oréal Research and Innovation, Tours, France Background: We speculated that an emollient supplemented with a biomass of nonpathogenic bacteria such as Vitreoscilla filiformis (Vf), grown in a medium containing thermal spring water (LRP-TSW); (LRP-Vitreoscilla filiformis biomass [LRP-VFB]), could have a beneficial effect for patients with atopic dermatitis (AD). Patients and methods: This double-blind, randomized, comparative study was conducted with 60 patients with moderate AD. Before starting the study, participants were pretreated for 15 days with drug therapy to improve their SCORing Atopic Dermatitis (SCORAD) by at least 25%. On Day 1, the eligible patients were randomized to either the emollient containing LRP-VFB associated with mannose (Product A) or another emollient (product B) and were treated twice daily for 1 month. Recurrence of flare-ups and microbial communities were characterized from swabs taken at Day 1 and Day 28, under axenic conditions, from affected (AF) and proximal unaffected (UAF) skin areas. Results: At Day 1, the average SCORAD of each group and the microbial communities of AF and UAF areas for each participant were similar. One month after the end of the therapeutic treatment (Day 28), the average evolution of SCORAD at Day 28 compared to Day 1 of patients treated with product A was significantly lower than that of the patients treated with product B. A significantly increased level of Xanthomonas genus was noticed in the group treated with product A (versus product B). On the other hand, the level of Staphylococcus genus increased between Day 1 and Day 28 in the group treated with product B, but not in the group treated with product A. Interestingly, these differences were more pronounced for patients in relapse, and the associated SCORAD worsening was less in the group treated with product A versus the group treated with product B. Conclusion: This study demonstrated that a specific emollient containing a biomass of non-pathogenic bacteria Vf grown in a medium containing TSW and associated with a selected carbon source is able to normalize skin microbiota and significantly reduce the number and severity of flare-ups compared with another emollient. Keywords: skin microbiota, atopic dermatitis, emollient, Vitreoscilla filiformis, thermal spring water, Xanthomonas genus